2020
DOI: 10.1167/iovs.61.2.46
|View full text |Cite
|
Sign up to set email alerts
|

Role of Insulin-Like Growth Factor Binding Protein-3 in the Pathogenesis of Herpes Stromal Keratitis

Abstract: The goal of this study was to determine the role of insulin-like growth factorbinding protein-3 (IGFBP-3) in the pathogenesis of herpes stromal keratitis (HSK). METHODS. In an unbiased approach, a membrane-based protein array was carried out to determine the level of expression of pro-and anti-angiogenic molecules in uninfected and HSV-1 infected corneas. Quantitative RT-PCR and ELISA assays were performed to measure the amounts of IGFBP-3 at mRNA and protein levels. Confocal microscopy documented the localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Macrophages undergo oxidative phosphorylation and acquire anti-inflammatory properties( 128 ).IGF family plays an important immune function in inflammatory lung injury and may provide a therapeutic target for humans in response to COVID-19 outbreak.Last year, researchers demonstrated the inhibitory effect of IGF-1 on phagocytosis by alveolar epithelial cells, with enhanced phagocytic activity noted on IGF-1 blockade in asthmatic mice. This supports potential use of IGF-1 as a target in inflammatory pulmonary conditions( 129 ).…”
Section: The Hepatocyte Growth Factor (Hgf)supporting
confidence: 72%
“…Macrophages undergo oxidative phosphorylation and acquire anti-inflammatory properties( 128 ).IGF family plays an important immune function in inflammatory lung injury and may provide a therapeutic target for humans in response to COVID-19 outbreak.Last year, researchers demonstrated the inhibitory effect of IGF-1 on phagocytosis by alveolar epithelial cells, with enhanced phagocytic activity noted on IGF-1 blockade in asthmatic mice. This supports potential use of IGF-1 as a target in inflammatory pulmonary conditions( 129 ).…”
Section: The Hepatocyte Growth Factor (Hgf)supporting
confidence: 72%
“…In addition to the cytokines and chemokines required for inflammatory immune responses, this review also emphasizes the important role of glycoproteins, SP, HVEM, hypoxia, and microRNAs in HSK pathogenesis. We believe that more pathogenic factors will be found in future scientific work, such as insulin-like growth factor-binding protein-3, which is present in the epithelium and stroma of HSK developing corneas and protects from aggravation of the lesions (144). It is important to have more in-depth research on hypoxia, microRNA, SP, and other areas to find more effective therapeutic targets for HSK and reduce the blindness rate.…”
Section: Resultsmentioning
confidence: 99%
“… 56 In terms of corneal HSV-1 infection and consistent with our data, a previous study reported that OPN-deficient mice presented with a significant drop in the incidence and severity of herpes stromal keratitis (HSK) following corneal infection out to day 15 pi. 57 Whereas several factors known to contribute to or correlate with opacity and HSK were evaluated after OPN neutralization, including IL-1α, IL-6, CXCL1, CCL2, MMPs, and IGFBP-3, 58 61 MMP-8 was the only factor investigated that changed (increased) following anti-OPN treatment. In general, MMPs are zinc-binding proteolytic enzymes that are involved in degradation and remodeling of the extracellular matrix in tissues, including the cornea.…”
Section: Discussionmentioning
confidence: 99%